2015
DOI: 10.7732/kjpr.2015.28.3.321
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effect of Alpiniae officinarum Rhizoma Extract on Degranulation in RBL-2H3 Cells

Abstract: Alpiniae officinarum Rhizoma (the rhizome of Alpinia officinarum Hance, known as lesser galangal), a family of Zingiberaceae, has been used to reduce pain of infection and inflammatory diseases in Asian countries. The present study was focused to evaluate the inhibitory degranulation effect of Alpiniae officinarum Rhizoma extract in RBL-2H3 rat basophilic leukemia cells. Cell viability was measured by MTT assay. RBL-2H3 cells were stimulated by phorbol 12-myristate 13-acetate and calcium ionophore A23187. Mast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…As an inducer of basophils, phorbol 12-myristate 13-acetate (PMA) is a mitogen involved in various biological phenomena by directly binding to protein kinase C (PKC) at the cellular level [28][29][30]. Ionomycin is an ionophore that destroys intercellular concentration gradients by transferring divalent cations through lipophilic membranes [31,32]. It has been reported that when basophils are activated by PMA and ionomycin, the production of Th2-type cytokines such as IL-4 is induced through MAPK and activator protein-1 (AP-1), which are downstream signaling pathways activated following PKC phosphorylation [33].…”
Section: Of 17mentioning
confidence: 99%
See 1 more Smart Citation
“…As an inducer of basophils, phorbol 12-myristate 13-acetate (PMA) is a mitogen involved in various biological phenomena by directly binding to protein kinase C (PKC) at the cellular level [28][29][30]. Ionomycin is an ionophore that destroys intercellular concentration gradients by transferring divalent cations through lipophilic membranes [31,32]. It has been reported that when basophils are activated by PMA and ionomycin, the production of Th2-type cytokines such as IL-4 is induced through MAPK and activator protein-1 (AP-1), which are downstream signaling pathways activated following PKC phosphorylation [33].…”
Section: Of 17mentioning
confidence: 99%
“…PI activates the PKC pathway in RBL-2H3 cells, and PKC induces degranulation and the release of lipid mediators and cytokines. These mediators contribute to the initiation of allergic inflammatory responses [32,33]. Therefore, we evaluated whether isoscopoletin's reduction of IL-4 led to the inhibition of PKC, MAPK subunits (ERK, JNK, and p38), and AP-1 subunit (c-Fos and c-Jun) activation.…”
Section: Isoscopoletin Suppresses Activation Of Pkc Mapk and Ap-1 Sig...mentioning
confidence: 99%